Integrated optimization of inventory, replenishment and vehicle routing for a sustainable supply chain under carbon emission regulations. (20th September 2021) - Rout, Chayanika; Paul, Arjun; Kumar, Ravi Shankar; Chakraborty, Debjani; Goswami, Adrijit
Abstract: Integrated decision regarding routing plan for vehicles, inventory management and operational adjustments confer minimum cost and emission for a supply chain network. In view of the aforementioned facts, this paper develops a sustainable supply chain inventory management (SSCIM) model for a single-vendor and multiple-buyers' integrated approach considering item deterioration and imperfect production simultaneously. A fleet of vehicles available at the vendor location are assigned to serve the buyers. Emissions generated through production, rework, transportation, warehousing and disposal of deteriorated items are taken into consideration. For the purpose of a cleaner and sustainable environment, several emission regulatory policies, namely, carbon tax, carbon cap-and-offset and cap-and-trade, are implemented so as to alleviate the effect of carbon emission by reducing its volume. The aforesaid scenarios are mathematically formulated in a bi-objective framework minimizing both total cost and overall emissions simultaneously subject to a well-built set of constraints. The bi-objective SSCIM focuses on obtaining a trade-off between cost and emissions, thereby determining the optimal production–shipment policy and a proper routing plan for the fleet of vehicles. For better illustration of the developed theory, numerical experiments are also carried out followed by an extensive discussion on the sensitivity analysis for various parameters. Highlights: Sustainable single vendor and multiple buyers' supply chain model is developed. Item deterioration and imperfect production are considered with rework facility. An efficient vehicle route-scheduling is designed to serve the buyers. Carbon emission regulation strategies are discussed. A constrained bi-objective optimization problem is formulated.